Increase risk of allergic diseases in patients with ankylosing spondylitis: A 10-year follow-up population-based study in Taiwan. Issue 45 (November 2016) - Chang, Wei-Pin; Kuo, Chun-Nan; Kuo, Li-Na; Wang, Yao-Tung; Perng, Wuu-Tsun; Kuo, Ho-Chang; Wei, James Cheng-Chung
Abstract : Abstract: Th2 and Th17 cells are both associated with developing ankylosing spondylitis (AS) and asthma. Th2 cells are also associated with allergic rhinitis and atopic dermatitis (AD). The prevalence of such allergic diseases in AS patients is unknown. In this study, we intended to study the risk of allergic diseases in a 10-year follow-up population of newly diagnosed patients with AS. We used a nationwide 10-year population-based database retrieved from the Longitudinal Health Insurance Database 2005 (LHID2005) in Taiwan. The study cohort comprised 857 patients with AS who had at least 1 claim of inpatient admission or at least 2 claims of ambulatory visit. The comparison cohort consisted of 4285 randomly selected subjects matched with AS group at a ratio of 5:1. We used Cox proportional-hazards regression to determine the 10-year disease-free survival rates after adjusting for potentially confounding factors. The AS patients had a 1.31 times greater risk of developing asthma within 10 years of diagnosis when compared with non-AS age- and sex-matched subjects, after adjusting for other risk factors (95% confidence interval = 1.00–1.75). But the difference was not significantly different. The AS patients also had a 1.46 times and a 1.22 times greater risk of developing allergic rhinitis and AD significantly. AS patients also had a lower allergic disease-free survival rate compared to non-AS group. Our results showed that patients with AS had a higher risk of developing allergic diseases later in life.